Overview of ongoing cohort and dietary studies in the Arctic - Weihe, Pál; Bjerregaard, Peter; Bonefeld-Jørgensen, Eva; Dudarev, Alexey; Halling, Jónrit; Hansen, Solrunn; Muckle, Gina; Nøst, Therese Haugdahl; Odland, Jon Øyvind; Petersen, Maria Skaalum; Rautio, Arja; Veyhe, Anna Sofia; et al. (International Journal of Circumpolar Health, 2017)
Published version. Source at http://dx.doi.org/10.3402/ijch.v75.33803 This article gives an overview of the ongoing cohort and dietary studies underlying the assessment of population health in the Arctic. The emphasis here is on a description of the material, methods and results or preliminary results for each study. Detailed exposure information is available in an article in this journal, whereas another paper describes the effects associated with contaminant exposure in the Arctic. The cohort descriptions have been arranged geographically, beginning in Norway and moving east to Finland, Sweden, Russia and the other Arctic countries and ultimately to the Faroe Islands. No cohort studies have been reported for Alaska or Iceland.